Efficacy and Safety of Chinese Herbal Medicine Xiao Yao San in Functional Gastrointestinal Disorders: A meta-Analysis and Trial Sequential Analysis of Randomized Controlled Trials - Liu, Qian; Shi, Zongming; Zhang, Tao; Jiang, Tianyuan; Luo, Xiaoying; Su, Xiaolan; Yang, Yang; Wei, Wei (Frontiers in Pharmacology, 2022)
Background and Aims: Functional gastrointestinal disorders are now named disorders of gut-brain interaction (DGBI) according to the Rome IV criteria, characterized by the interaction of gastrointestinal symptoms and dysregulation of central nervous systems. Xiao-Yao-San (XYS) is effective in the treatment of gastrointestinal symptoms in China, especially in patients with concurrent mood disorders. A meta-analysis was designed to evaluate the efficacy and safety of Xiao-Yao-San for FGIDs. Methods: We searched randomized controlled trials in seven databases from their inception till November 22, 2021. Pooled analysis included therapeutic efficacy, symptom score, Self-Rating Anxiety Scale (SAS) score, Self-Rating Depression Scale (SDS) score, and the recurrence rate. Conventional meta-analysis with random-effects model or fixed-effects model and trial sequential analysis (TSA) were performed. Results: A total of 48 RCTs were eligible for inclusion (n = 4,403). Meta-analysis results showed that XYS could improve the effective rate of FGIDs compared with western drugs [RR = 1.23; (95%CI, 1.19–1.27); p < 0.00001], and XYS combined with western medicine could also improve the effective rate [RR = 1.26; (95%CI, 1.21–1.33); p < 0.00001]. In addition, XYS could reduce the symptom score [SMD = −1.07; (95%CI −1.42, -0.72); Z = 6.03; p < 0.00001], SAS score [MD = −6.24; (95%CI −7.48, −4.99); Z = 9.81; p < 0.00001] and SDS score [MD = -6.70; (95%CI −8.18, −5.21); Z = 8.83; p < 0.00001] of FGIDs patients, and reduce the recurrence rate [MD = -6.70; (95%CI −8.18, −5.21); Z = 8.83; p < 0.00001]. XYS was safe in most cases and no serious adverse events were observed in any of the included trials. TAS showed adequate “information size” for the primary outcome, and further confirmed the efficacy of XYS in the treatment of FGIDs. Conclusion: XYS could improve symptoms and reduce recurrence rates in FGIDs patients, and XYS may be a potential candidate for the treatment of FGIDs. However, due to the limited quality of current studies, more long-term, randomized, double-blinded clinical trials are needed in future studies. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=284308, identifier CRD42021284308.